Administrasi Pemerintahan Khalifah ‘Umar Ibn al-Khatth?b:: Sebuah Tinjauan Sekilas - Muhammad Hasyim; Muhammad Husni (Fakultas Syariah - IAI Al-Qolam Malang, 2018)
In his relatively brief reign, ‘Umar ibn al-Khatthab had made many innovative breakthroughs including those relating to government administration. All of this was done in order to answer the increasingly rapid and complex developments along with the increasing breadth of the Islamic region and the increasingly plural socio-cultural community. These innovations, among others, include the fields of government administration, economics, justice, and military affairs. Interestingly, most of the breakthroughs were the result of the creativity of his thoughts, not from the textual guidance of the Prophet Muhammad SAW. In fact, some of them are contrary to the policies of the previous period.